Islamic sustainable finance: Gulf experiences - Adam Sa'ad, Auwal; Usman, Abubakar; Rehan, Raja (Routledge, 2024)
The concept of Islamic Sustainable development has been the focus of Muslim economist and rulers throughout the history of Islamic Civilisation. One of the Prophet Muhammad's mission was to enlighten people on the sustainability of the earth's resources.